2009
DOI: 10.1111/j.1440-1584.2009.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

What stresses remote area nurses? Current knowledge and future action

Abstract: There is a lack of empirical evidence relating to stresses experienced by RANs. The literature identifies some of the stresses experienced by RANs as unique to the remote context, while some are related to high demands coupled with a deficit of appropriate resources. Use of models, such as the JD-R model of occupational stress, might assist in identifying key areas where resources can be enhanced to better meet the high level of need and reduce RANs' levels of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 28 publications
1
56
0
Order By: Relevance
“…The inability to meet high clinical demand has been associated with emotional exhaustion in remote area nurses [40]. Lenthall et al, (2009) suggest that this situation is “exacerbated by a low-resource environment” [41] but results of this study did not identify resources as a significant contributor to retention for either allied health cohort.…”
Section: Discussionmentioning
confidence: 62%
“…The inability to meet high clinical demand has been associated with emotional exhaustion in remote area nurses [40]. Lenthall et al, (2009) suggest that this situation is “exacerbated by a low-resource environment” [41] but results of this study did not identify resources as a significant contributor to retention for either allied health cohort.…”
Section: Discussionmentioning
confidence: 62%
“…McGrath et al (2003) consider colleagues' support as a factor for decreasing stress 9) . Other studies found that the following strategies can decrease the amount of stress experienced by nurses: giving value to nurses' opinions, and respecting their profession 27) , talking to intimate friends, interpersonal and organizational communication 25) , colleague's support, appropriate training, and attending conferences to get upto-date information 29) , maintaining social interaction, getting help from the colleagues 4) , having a sense of importance due to the support of superiors and colleagues 1) , creating an appropriate working situation by nurse managers 30) , and effective interaction among nurses 31) . The core category in this study was "On the route to coping" used to explain the overall phenomenon of nurses coping with job stress.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need in these settings for the provision of essential education, training and other professional development opportunities for nurses and ensuring access (Francis, Bowman, & Redgrave, 2001). It is encouraging to note that over recent years there have been improvements in these opportunities (Lenthall et al, 2009) but some barriers to accessing these remain. Despite the project offering tobacco local cessation training, few sessions have been delivered by nurses who struggle to fi nd time to take advantage of the training they receive.…”
Section: Implications For Remote Area Nurses: a Call To Armsmentioning
confidence: 99%
“…A major challenge for remote area nurses in many communities is the high level of morbidity (Lenthall et al, 2009) resulting in prioritisation of acute care. The need for nurses to focus on acute care problems limits the time they have to devote to addressing chronic health problems such as tobacco use.…”
Section: Implications For Remote Area Nurses: a Call To Armsmentioning
confidence: 99%